A Novel Approach for Building Adaptive Components using Top-Down Analysis - Korra, Sampath; Vasumathi, D.; Vinaybabu, A. (International Journal of Engineering and Technology, 2018)
Developing reusable components are one of the main objectives of component-based software engineering. They play a crucial role in the field of application development and support. CBSE use certain architectural patterns and infrastructures of standard software to increase overall product quality. CBSE apply two parallel engineering activities, domain engineering and component-based development (CBD). Domain analysis explores the application domain with the intent of finding functional, behavioural, and data components that are candidates for reuse and places them in the reuse repository. Strategies for developing adaptive reusable components using top-down domain analysis leads to good quality in the component. Domain analysis promotes strategies and models that have been developed for their specific areas. Therefore, these models are suitable for their own domain, but may not be entirely suitable for domain analysis of other domains. So, developing the reusable components using the top down domain analyses existing components. This paper describes how to build a domain to use top-down analysis of reusable software components.Â Â